Graph Manipulation and the Impact on Pre-Service Teachers' Accuracy in Evaluating Progress Monitoring Data. (February 2023) - Kuntz, Emily M.; Massey, Cynthia C.; Peltier, Corey; Barczak, Mary; Crowson, H. Michael
Through time-series graphs, teachers often evaluate progress monitoring data to make both low- and high-stakes decisions for students. The construction of these graphs—specifically, the presence of an aimline and the data points per x - to y -axis ratio (DPPXYR)—may impact decisions teachers make. The purpose of this study was to evaluate the impact of graph construction manipulations on pre-service teachers' accuracy with instructional decision-making. Participants included 94 pre-service teachers enrolled in an introductory course focused on students with disabilities at two universities. Following instruction on progress monitoring, students evaluated 48 graphs representing eight data sets with six manipulations (i.e., with and without aimline; DPPXYR set at 0.05, 0.10, 0.15). Results suggest that the presence of an aimline increased accuracy, whereas the manipulation of the DPPXYR led to mixed findings. Implications for future research and practice are discussed.